A Framework for Incorporating Patient Preferences to Deliver Participatory Medicine via Interdisciplinary Healthcare Teams - Kuziemsky, Craig (AMIA Annu Symp Proc, 2014)
Participatory medicine refers to the equal participation of patients and interdisciplinary healthcare team (IHT) members as part of care delivery. Facilitating workflow execution is a significant challenge for participatory medicine because of the need to integrate IHT members into a common workflow. A further challenge is that patient preferences should be considered when executing a workflow. To date there is limited research on supporting patient workflow as part of participatory medicine practices. To address that shortcoming we used a two-phase approach to develop a framework for participatory medicine that integrates different IHT members and workflows including the incorporation of patient preferences about care delivery options. Our framework uses a domain ontology to define the patient, IHT concepts and relations, as well as a workflow for operationalizing participatory medicine via an IHT. Proof of concept of the proposed framework is illustrated with a palliative care pain management case study.